Penelitian Komparatif Mengenai Pengelolaan Sampah Di Daya Tarik Wisata Pantai Candikusuma Jembarana Dan Pantai Kuta Badung - Loviannauli P, Theresia; Nugroho, Saptono (JURNAL DESTINASI PARIWISATA; Vol 9 No 2 (2021): VOL 9, NO 2 (2021): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2021.v09.i02.p17, 2021)
The purposes of this study are to compare the waste management system used in the Tourism Attraction of Candikusuma Beach Jembrana and Kuta Beach Badung, and to compare each waste management system. Comparisons are made to find out the similarities, differences, advantages and disadvantages of each waste management system. The method used in this research is qualitative. This type of research is a comparative study. The data source used is a secondary data source. This research is based on research results from Prabawa (2019) and Megawan (2018) research. The results of this study show that the waste management system at Candikusuma Beach Jembrana uses a 3R waste management system (Reduce, Reuse, Recycle), while Kuta Beach Badung uses a 4P waste management system (Sorting, Processing, Collecting, Transporting). There are similarities and differences in the two waste management systems, and there are also weaknesses and strengths of each waste management system. Keyword: Waste Management, Comparative Research, Beach Tourist Attraction